Mr. Associated Press : Kent Cooper and the twentieth-century world of news - Allen, Gene, 1952- (History of communication., 2023)
"Between 1925 and 1951, Kent Cooper transformed the Associated Press, making it the world's dominant news agency while changing the kind of journalism that millions of readers in the United States and other countries relied on. Gene Allen's biography is a globe-spanning account of how Cooper led and reshaped the most important institution in American--and eventually international--journalism in the mid-twentieth century. Allen critically assesses the many new approaches and causes that Cooper championed: introducing celebrity news and colorful features to a service previously known for stodgy reliability, pushing through disruptive technological innovations like the instantaneous transmission of news photos, and leading a crusade to bring American-style press freedom--inseparable from private ownership, in Cooper's view--to every country. His insistence on truthfulness and impartiality presents a sharp contrast to much of today's fractured journalistic landscape. Deeply researched and engagingly written, Mr. Associated Press traces Cooper's career as he built a new foundation for the modern AP and shaped the twentieth-century world of news"--